Prevalence and cost of hospitalized patients with asymptomatic COVID-19 in 2020 in Spain - Álvarez-del Río, Blanca; Sánchez-de Prada, Laura; Álvaro-Meca, Alejandro; Martín-Fernández, Marta; Álvarez, F. Javier; Tamayo, Eduardo; Gutiérrez-Abejón, Eduardo (Frontiers in Public Health, 2023)
Introduction:COVID-19 has been characterized by the presence of asymptomatic patients. Additionally, most studies evaluating costs focus on symptomatic COVID-19 cases. Objective: To describe the prevalence, characteristics, and costs of asymptomatic COVID-19 cases at admission in Spanish hospitals in 2020. Methods: A nationwide study included data of hospitalized patients collected from the Minimum Basic Data Set(MBDS) in Spain during 2020. Patients with COVID-19 codes as a primary and as a secondary diagnosis at admission were selected. Variables collected included age, sex, length-of-stay, in-hospital death, admission, length-of-stay and death in intensive care unit(ICU), mechanical ventilation and ventilatory assistance. COVID-19 related hospital costs were calculated using diagnosis-related groups from the MBDS. Patients and costs were disaggregated by sex, age, ICU admission and epidemic wave(first or second) and main diagnosis. Results: A total of 14,742 patients were admitted with asymptomatic COVID-19 in Spanish hospitals representing 6.35% of all COVID-19 admitted patients. The total cost of admissions with asymptomatic COVID-19 was €105,933,677.6 with a mean cost per patient of €7,185.8, higher in the first wave despite only 2.7% of cases were found then. Based on primary diagnosis, the higher number of cases of asymptomatic COVID-19 were found in “Pregnancy, childbirth and the puerperium” followed by “diseases of the circulatory system” Conclusions: There was a high prevalence of asymptomatic cases during screening at admission process in Spanish hospitals in 2020, specially in those groups. The higher costs might be due to the main pathology and the associated healthcare provisions needed in case of positive COVID-19 testing.